2012
DOI: 10.1158/1538-7445.am2012-3483
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3483: Inhibition of Monocarboxylate Transporter 4 (MCT4) targets stem-like cells in glioblastoma

Abstract: Glioblastomas (GBM) are the most common adult malignant brain tumors and contain a hypoxic/necrotic core surrounded by proliferative cells. To unmask genes important in hypoxia, we exposed 2 GBM neurosphere lines, HSR-GBM1 and JHH-GBM10, to 1% and 21% oxygen levels for 24 hours and compared gene expression using Agilent oligonucleotide microarrays. We identified SLC16A3 (Monocarboxylate transporter-4, MCT4) as one of the most upregulated genes in response to hypoxia. To investigate the clinical importance of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…This finding is supported by a study in which an increased lactate transport via monocarboxylate transporters (MCT1-4) was found in glioma stem-like cells [39]. Moreover, previous studies showed an upregulation of MCT4 in GBM neurospheres [5].…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…This finding is supported by a study in which an increased lactate transport via monocarboxylate transporters (MCT1-4) was found in glioma stem-like cells [39]. Moreover, previous studies showed an upregulation of MCT4 in GBM neurospheres [5].…”
Section: Discussionsupporting
confidence: 57%
“…In particular, GBM cells located at the resection margin were shown to proliferate rapidly, and to be more invasive than GBM cells at the center of the tumor [31,32]. With regards to the dormancy phenomenon and the slightly increased expression of the dormancy markers EPHA5 and IGFBP5 at the edge of the tumor observed in our study, the only connection published to date is an induction of MCT4 and dormancy markers by hypoxia [5,33]. The current understanding of GBM suggests that up to 50% of the tumor mass is generated by the tumor stroma.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations